16S rRNA gene-based identification of cultured bacterial flora from host-seeking Ixodes ricinus, Dermacentor reticulatus and Haemaphysalis concinna ticks, vectors of vertebrate pathogens - Rudolf, Ivo; Mendel, Jan; Šikutová, Silvie; Masaříková, J; Nováková, Dana; Buňková, Leona; Sedláček, Ivo; Hubálek, Zdeněk; Švec, Pavel (Folia microbiologica, 2009)
A total of 151 bacterial isolates were recovered from different developmental stages (larvae, nymphs and adults) of field-collected ticks (67 strains from Ixodes ricinus, 38 from Dermacentor reticulatus, 46 from Haemaphysalis concinna). Microorganisms were identified by means of 16S rRNA gene sequencing. Almost 87 % of the strains belonged to G(+) bacteria with predominantly occurring genera Bacillus and Paenibacillus. Other G(+) strains included Arthrobacter, Corynebacterium, Frigoribacterium, Kocuria, Microbacterium, Micrococcus, Plantibacter, Rhodococcus, Rothia, and Staphylococcus. G(-) strains occurred less frequently, comprising genera Advenella, Pseudomonas, Rahnella, Stenotrophomonas, and Xanthomonas. Several strains of medical importance were found, namely Advenella incenata, Corynebacterium aurimucosum, Microbacterium oxydans, M. schleiferi, Staphylococcus spp., and Stenotrophomonas maltophilia. Data on cultivable microbial diversity in Eurasian tick species D. reticulatus and H. concinna are given, along with the extension of present knowledge concerning bacterial flora of I. ricinus.
Keywords: financování organizované; Animals; ribozomální DNA; Female; DNA, Ribosomal; arachnida jako vektory; infestace klíšťaty; ženské pohlaví; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; Molecular Sequence Data; Ixodidae; Financing, Organized; Phylogeny; molekulární sekvence - údaje; Male; Bacteria; Vertebrates; Bacterial Typing Techniques; techniky typizace bakterií; obratlovci; zvířata; mužské pohlaví; Arachnid Vectors; fylogeneze; Tick Infestations; RNA ribozomální 16S